Antitumor effect of 4MU on glioblastoma cells is mediated by senescence induction and CD44, RHAMM and p-ERK modulation - Pibuel, Matías Arturo (2021)
The extracellular matrix plays a key role in cancer progression. Hyaluronan, the main glycosaminoglycan of the extracellular matrix, has been related to several tumor processes. Hyaluronan acts through the interaction with cell membrane receptors as CD44 and RHAMM and triggers signaling pathways as MEK/ERK. 4-methylumbelliferone (4MU), a well-known hyaluronan synthesis inhibitor, is a promising alternative for cancer therapy. 4MU is a coumarin derivative without adverse effects that has been studied in several tumors. However, little is known about its use in glioblastoma (GBM), the most malignant primary brain tumor in adults. Glioblastoma is characterized by fast growth, migration and tissue invasiveness, and a poor median survival of the patients after treatment. Several reports linked glioblastoma progression with HA levels and even with CD44 and RHAMM expression, as well as MEK/ERK activation. Previously, we showed on a murine GBM cell line that HA enhances GBM migration, while 4MU markedly inhibits it. In this work we showed for the first time, that 4MU decreases cell migration and induces senescence in U251 and LN229 human GBM cell lines. Furthermore, we observed that HA promotes GBM cell migration on both cell lines and that such effects depend on CD44 and RHAMM, as well as MEK/ERK signaling pathway. Interestingly, we observed that the exogenous HA failed to counteract the effects of 4MU, indicating that 4MU effects are independent of HA synthesis inhibition. We found that 4MU decreases total CD44 and RHAMM membrane expression, which could explain the effect of 4MU on cell migration. Furthermore, we observed that 4MU increases the levels of RHAMM inside the cell while decreases the nucleus/cytoplasm relation of p-ERK, associated with 4MU effects on cell proliferation and senescence induction. Overall, 4MU should be considered as a promising therapeutic alternative to improve the outcome of patients with GBM.